2016
DOI: 10.2174/1874372201610010055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-Infections in Lyme Disease

Abstract: Lyme disease is one of the most frequent tick-borne diseases worldwide, it can be multi-systemic and insidious, in particular when it shows a chronic course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Lyme disease and its associated co-infections, including Babesia and Bartonella, are increasingly being reported in the medical literature as potential overlapping factors leading to chronic resistant symptomatology [14,38,39,63,73,234,235], where combination antibiotics effectively relieve tick-borne infection (TBI) symptoms, with good patient tolerance [236]. Our three patients with Borrelia, Bartonella, and/or Babesia, described in these case reports, all had excellent outcomes with short-term combination antibiotics, using pulsed persister drug regimens with biofilm agents.…”
Section: Discussionmentioning
confidence: 99%
“…Lyme disease and its associated co-infections, including Babesia and Bartonella, are increasingly being reported in the medical literature as potential overlapping factors leading to chronic resistant symptomatology [14,38,39,63,73,234,235], where combination antibiotics effectively relieve tick-borne infection (TBI) symptoms, with good patient tolerance [236]. Our three patients with Borrelia, Bartonella, and/or Babesia, described in these case reports, all had excellent outcomes with short-term combination antibiotics, using pulsed persister drug regimens with biofilm agents.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in various regions have documented the co-infection of multiple tick-borne pathogens ( Hersh et al., 2014 ). Co-infection of multiple tick-borne diseases becomes an emerging problem since the interaction of these pathogens may affect the severity and duration of symptoms in humans, making diagnosis and treatment more challenging ( Hersh et al., 2014 , Stinco and Bergamo, 2016 , Thompson et al., 2001 ). For example, simultaneous Lyme disease and human babesiosis is shown to be correlated with a more severe clinical progression and persistent symptoms than either condition alone ( Adelson et al., 2004 , Diuk-Wasser et al., 2016 , Hersh et al., 2014 ).…”
Section: Co-infection Of Ixodes Tick-borne Pathogementioning
confidence: 99%
“…Children with PANS often have elevations in antineuronal antibodies against lysoganglioside [32], tubulin [33], and dopamine receptors [34][35][36], as well as activation of calcium Calmodulin-Dependent Protein Kinase II (CaMKII) [37]. CaMKII alters dopamine pathways, which in turn can lead to neuropsychiatric symptoms [37,38] In fact, it is likely that the preponderance of patients with persistent symptoms of Lyme disease despite treatment for B. burgdorferi have coinfections [57][58][59][60][61]. Coinfection of ticks is now "the rule rather than the exception", as highlighted by Moutailler, et al [62] who found that coinfections occurred in almost half of all infected Ixodes ticks in the French Ardennes; single ticks had up to fi ve diff erent pathogens.…”
mentioning
confidence: 99%